Identification of Natural Products as SENP2 Inhibitors for Targeted Therapy in Heart Failure - Taghvaei, Somayye; Sabouni, Farzaneh; Minuchehr, Zarrin (Frontiers in Pharmacology, 2022)
Sentrin-specific protease -2 (SENP2) is involved in deSUMOylation. Increased deSUMOylation in murine hearts by upregulated SENP2 resulted in cardiac dysfunction and congenital heart defects. Natural compounds via regulating cell proliferation and survival, induce cell cycle cessation, cell death, apoptosis, and produce reactive oxygen species and various enzyme systems consisting of mitochondrial electron transfer chains, cytochrome lipoxygenase, cyclooxygenase, and NADPH oxidase complexes cause disease prevention. In order to SENP2 inhibition by natural products, we were done molecular docking and molecular dynamics simulation of natural compounds Gallic acid (GA), Caffeic acid (CA), Thymoquinone (TQ), Betanin, Betanidin, Fisetin, and Ebselen. The toxicity of compounds was also predicted. The results showed Betanin constitutes a stable complex with SENP2 active site because, Betanin showed low RMSD and high binding energy and hydrogen bonds. As well as, this compound demonstrated the lowest toxicity even less than Ebselen. Betanin constituted a stable complex with SENP2 with 4-7 hydrogen bonds and also constituted more stable MD plots even than Ebselen. Then, Betanin can be a suitable compound for SENP2 inhibition and for heart failures treatment and the clinical studies can conduct for verifying its role in vivo and in vitro.